1981
DOI: 10.2134/agronj1981.00021962007300040010x
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition of Grain Protein of Maize Grown with and without Pesticides and Standard Commercial Fertilizers1

Abstract: Increases in the price of agricultural chemicals and uncertain supplies are likely to cause a reduction of pesticide and fertilizer use in the future. Therefore, it is of interest to compare yields and quality of crops grown under present conventional practice with those grown at the lower limit of chemical intensiveness. In this paper, we report measurements of the amino acid composition of protein from maize (Zea mays L.) grain raised on 14 pairs of fields which did (conventional) and which did not (organic)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…for bread-making) and that optimized fertilization practices can maintain reasonably high protein levels. Moreover, a 25-30% increase in lysine has been reported in organic wheat (Wolfson and Shearer, 1981;Brandt et al, 2000). Comparative studies performed on hen eggs (Kouba, 2002) and raw cow's milk (Toledo et al, 2002) did not show any noticeable difference in protein levels.…”
Section: Macronutrient Contentsmentioning
confidence: 95%
“…for bread-making) and that optimized fertilization practices can maintain reasonably high protein levels. Moreover, a 25-30% increase in lysine has been reported in organic wheat (Wolfson and Shearer, 1981;Brandt et al, 2000). Comparative studies performed on hen eggs (Kouba, 2002) and raw cow's milk (Toledo et al, 2002) did not show any noticeable difference in protein levels.…”
Section: Macronutrient Contentsmentioning
confidence: 95%
“…"It is considered that such higher-protein corn is superior feed-stuff." The results for maize, reported by Lockeretz et al (1981) and by Wolfson and Shearer (1981), showed that the crude protein concentration in a conventionally grown crop was significantly higher than that in the organically grown crop. One study has actually shown processed organic products to be less healthy than their conventionally produced equivalents.…”
Section: Organic Food Is More Nutritious?mentioning
confidence: 93%
“…This wavenumber can be associated to the C]O's side chain in aspartic acid and glutamic acid (Barth, 2000). Both aspartic acid and glutamic acid are shown to be present in higher amounts in conventionally grown corn versus organically grown corn (Wolfson and Shearer, 1981). The nitrogen that is present in the fertilizer used to grow conventional crops causes increased concentration and yield of proteins (Wolfson and Shearer, 1981).…”
Section: Classification Analysismentioning
confidence: 99%